Body mass index is associated with higher Gleason score and biochemical recurrence risk following radical prostatectomy in Chinese men: a retrospective cohort study and meta-analysis. Issue 1 (December 2015) - Bai, Pei-De; Hu, Meng-Bo; Xu, Hua; Zhu, Wen-Hui; Hu, Ji-Meng; Yang, Tian; Jiang, Hao-Wen; Ding, Qiang
Abstract Background The aim of the study is to investigate whether body mass index (BMI) affected pathological characteristics and biochemical recurrence (BCR) of prostate cancer after radical prostatectomy in Chinese men. Methods Medical records of 211 Chinese patients who underwent radical prostatectomy between 2006 and 2014 were retrospectively reviewed, with follow-up time of 24.5 ± 27.0 months. Multivariate logistic and Cox regression analyses were applied to address the impact of BMI on adverse pathological outcomes and BCR following prostatectomy. A meta-analysis of published studies from MEDLINE or EMBASE was conducted to determine the relationship between BMI and BCR following prostatectomy among Asian populations. Results Higher BMI was positively correlated with higher biopsy Gleason score (odds ratios (OR) 1.163, 95 % confidence interval (CI) 1.023–1.322, P  = 0.021) and pathological Gleason score (OR 1.220, 95 % CI 1.056–1.410, P  = 0.007) in multivariate analysis. BCR was detected in 48 patients (22.7 %). Multivariate Cox proportional hazards analysis revealed that higher BMI (hazard ratio (HR) 1.145, 95 % CI 1.029–1.273, P  = 0.013) and prostate-specific antigen (HR 1.659, 95 % CI 1.102–2.497, P  = 0.015) levels were independent predictors of BCR. The meta-analysis enrolled eight Asian studies of 4145 patients treated by radical prostatectomy. Based on random-effects approach, a 5 kg/m2 increase in BMI was correlated with 28 % higher risk of BCR (HR 1.22, 95 % CI 0.86–1.72) without statistical significance. Conclusions The present study suggested that higher BMI was an independent risk factor for a higher Gleason score, as well as an independent predictor of BCR after radical prostatectomy in Chinese patients. Meta-analysis of Asian studies also indicated that obese patients, although without statistical significance, might be more likely to suffer from BCR.